Policy Transfer in Criminal Justice : Crossing Cultures, Breaking Barriers - McFarlane, Mary Anne.; Canton, Rob.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Will'what works' in one country work in another? This unique collection examines the cross-cultural transfer of skills and expertise, drawing out the opportunities and challenges involved in taking penal practices from one country to another.
Keywords: Social sciences; Europe -- Politics and government; Criminology; Juvenile delinquents; Corrections; Punishment; Religion and sociology; Social service; Social Sciences; Youth Offending and Juvenile Justice; Criminology & Criminal Justice; European Politics; Prison and Punishment; Social Care; Sociology of Religion